THE EFFECT OF HEALING ENVIRONMENT PRINCIPLES ON STRESS LEVEL OF COVID-19 PATIENTS : (CASE STUDY AT HOSPITAL X) - Cicilia Maria Ernawati; I Wayan Agus Wirya Pratama; Endy Wira Pradana; Engerlbertha Retno Suryaningati; Natasya Silvaira Harijanto; Tito Haripradianto (Universitas Brawijaya, 2022)
During the COVID-19 pandemic, hospitals are required to provide unique isolation rooms for confirmed COVID-19 patients. This study aims to determine the effect of the healing environment principle on designing an isolation room without a ventilator on the patient's stress level. This research is descriptive qualitative using Focused Group discussion with COVID-19 ex-patients. The study was conducted at Hospital X in May 2021. The results showed that the things that helped reduce stress in patients were the presence of a garden outside the isolation room and good quality linen, clean fragrance, and disinfectant, which made the patient confident about the cleanliness of the room. Meanwhile, what causes stress is the noise of the exhaust fan, dull paint color, lack of privacy in the isolation room, the smell of the bathroom that is not pleasant, and the food's taste is not good. This study concludes that the balance of natural and psychological elements in the arrangement of the COVID-19 isolation area and room can affect the thoughts, feelings, and behavior of patients treated in the COVID-19 isolation room.